Plasma S100P level as a novel prognostic marker of metastatic breast cancer - Peng, Cike; Chen, Hongda; Wallwiener, Markus; Modugno, Caroline; Cuk, Katarina; Madhavan, Dharanija; Trumpp, Andreas; Heil, Jörg; Marmé, Frederik; Nees, Juliane; Riethdorf, Sabine; Schott, Sarah; et al. (Breast cancer research and treatment, 2016)
Metastasis is the main cause of death in breast cancer patients. The development of reliable and cost-effective biomarker to evaluate the prognosis of metastatic breast cancer (MBC) patients is of great importance. S100P is a member of S100 family and has been proved to be associated with metastasis establishment. Methods: We investigated the plasma S100P levels in 60 healthy controls, 48 primary and 273 metastatic breast cancer patients. The MBC patients were followed-up for disease progression and death up to 3.5 years after recruitment. Radiographic response of MBC patients were also analyzed for investigation on treatment monitoring value of plasma S100P level. We found a robust association between high plasma S100P level (>7 ng/mL) and poor prognosis of metastatic breast cancer (MBC) patients (median progression-free survival time: 5.0 vs. 8.7 months, log-rank test p < 0.001; median overall survival time: 22.5 vs. 31.6 months, log-rank test p < 0.001). The plasma S100P level added additional prognostic relevance to the conventional prognostication model with clinicopathological factors and CTC enumeration. The plasma S100P level decreased significantly after treatment, while the reduction correlated with the radiographic response of the MBC patients. This finding indicates the value of plasma S100P in dynamic evaluation of treatment outcome. We hereby suggest plasma S100P level as a simple and cost-effective marker for the prognosis of metastatic breast cancer.
Published: 04 May 2016
Gesehen am 21.09.2020